Ruptured hepatocellular carcinoma: A case report and review of literature - KC, Sudeep; Poudyal, Himani (Journal of Chitwan Medical College, 2024)
Hemoperitoneum caused by nontraumatic liver rupture is rare. The spontaneous rupture of hepatocellular carcinoma can pose a serious threat to life, particularly in the absence of cirrhosis. Ruptured hepatocellular carcinoma (HCC) is a medical emergency with a high mortality rate, and diagnosing it can be challenging. Treatment options vary depending on resources and the stage of HCC. This case report focuses on the CT findings of a 52-year-old gentleman who was initially diagnosed with hemoperitoneum resulting from the spontaneous rupture of HCC at the emergency department. The patient underwent trans-arterial embolization (TAE) for hemostasis. Timely identification and intervention for ruptured HCC are essential. This particular case underscores the importance of early detection and immediate treatment for ruptured HCC. This case report delves into an instance of spontaneous HCC rupture in a patient without liver cirrhosis. While radiological imaging plays a crucial role in confirming the diagnosis. It also helps in treatment plans which include consideration of surgical, and interventional procedures as well as chemotherapy.